2006
DOI: 10.1179/135100006x116592
|View full text |Cite
|
Sign up to set email alerts
|

The combined luminol/isoluminol chemiluminescence method for differentiating between extracellular and intracellular oxidant production by neutrophils

Abstract: To address the question why isoluminol, but not luminol, failed to detect oxidants produced intracellularly, differences between these luminophores were investigated with respect to physicochemical parameters and the character of chemiluminescence signal. Our results showed the isoluminol molecule to be more polar, more hydrophilic and possessing lower ability to form intramolecular bonds than the luminol molecule. Therefore, isoluminol: (i) only slightly pervaded biological membranes; (ii) depended essentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…This difference could be related to the fact that isoluminol only detects extracellular production of reactive species [72]. The extracellular origin of isoluminol chemiluminescence was also confirmed by its almost complete blockade in the presence of SOD and catalase [80]. Since the response to PMA as well as to fMLP was almost totally inhibited by SOD, Lundqvist and Dahlgren [76] concluded that isoluminol mainly detects cellular release of O 2…”
Section: Isoluminolmentioning
confidence: 88%
See 2 more Smart Citations
“…This difference could be related to the fact that isoluminol only detects extracellular production of reactive species [72]. The extracellular origin of isoluminol chemiluminescence was also confirmed by its almost complete blockade in the presence of SOD and catalase [80]. Since the response to PMA as well as to fMLP was almost totally inhibited by SOD, Lundqvist and Dahlgren [76] concluded that isoluminol mainly detects cellular release of O 2…”
Section: Isoluminolmentioning
confidence: 88%
“…Isoluminol differs from luminol not with respect to the basic mechanism for generation of light but only in respect to the position of the amino group in the phthalate ring of the molecule, which makes isoluminol less lipophilic and thus less permeable to biological membranes than luminol (Fig. 3) [76,80]. In general, the intensity of isoluminol-enhanced chemiluminescence in leukocytes stimulated by different activators is markedly lower when compared with luminol-enhanced chemiluminescence [72].…”
Section: Isoluminolmentioning
confidence: 90%
See 1 more Smart Citation
“…Next, we analyzed the activity of the cells by measuring the luminol-mediated chemiluminescence (detecting both intra-and extracellular ROS) 42 cell types that adhere to the surface of implants after insertion in vivo. The oxidative response and secretion of molecules are influenced by both the properties of the material and the component of their microenvironment.…”
Section: Monocyte Activation In Response To Different Substrates and mentioning
confidence: 99%
“…This difference between the two molecules does not change the light-generating mechanism, even though the physicochemical properties differ and the quantum yield from luminol is somewhat higher than that of isoluminol (3). Isoluminol is more hydrophilic since the polarity increases as the amino group moves away from the first carbon atom (2,4). As a consequence, isoluminol is less able to transverse biological membranes and is therefore used to detect the release of NADPH oxidase-derived superoxide ions.…”
Section: Introductionmentioning
confidence: 94%